Myocardial Perfusion Imaging Using 99mTc-MIBI Single Photon Emission Computed Tomography: A Cardiac Phantom Study - Al Moudi, Mansour; Sun, Zhonghua (American Scientific Publishers, 2013)
This study tests myocardial perfusion imaging on a thorax-heart phantom by using 99mTc-MIBI SPECT undernormal and simulated myocardial perfusion conditions. A thorax-heart phantom was designed to serve as purposeof performing myocardial perfusion imaging. The phantom consists of left and right ventricles, vertebralcolumn and lungs. A number of inserts with variable sizes were placed in the left ventricular wall to simulatemyocardial infarcts. All phantom image acquisitions were performed on a three-head SPECT/CT camera. RestSPECT myocardial perfusion imaging was successfully performed on the cardiac phantom with demonstrationof normal left myocardium and infarcted areas. The simulated infarcted areas were clearly visualised on shortand long-axis slices in the left ventricular wall. The phantom can be used for further experiments to investigatethe low-dose protocol of SPECT and PET myocardial perfusion imaging.